Strategi guru menumbuhkan Cinta Membaca pada anak PAUD dan SD - Dzulaekha, Annisah Nurul; Iswatiningsih, Daroe; Ulzana, Yuhanita; Astuti, Rina Dwi (Borobudur Educational Review, 2025)
Reading is a crucial skill for children's cognitive, social, and emotional growth, yet interest in reading is waning in the digital age. This study investigates interactive reading strategies to enhance engagement in early childhood and elementary students, employing qualitative methods such as observation and interviews. It involved children aged 4-12 during a month-long reading program. Key findings demonstrate that techniques like storytelling, role-playing, open-ended questions, story mapping, paired reading, and book creation significantly boost children's focus and comprehension. The research supports Vygotsky’s social learning theory and Deci & Ryan’s self-determination theory, which highlight the importance of autonomy and relatedness in motivation. Despite some limitations, the study suggests that interactive reading can effectively enrich early literacy in educational environments.